2019
DOI: 10.15282/ijame.16.1.2019.25.0487
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behaviour and Characteristics of Rubber Blade Car Performance

Abstract: High technologies have helped so much in improving an optimizing the engine design and performance of the car. Improved isolation has helped to minimize the engine noise making other automotive part noises become more detectable. One of the noise sources are the wipers. When a wiper operates on a windshield, vibratory phenomena may appear due to flutter instabilities and may generate squeal noise. In order to obtain good wiping behaviour and characteristics, the rubber blade should be in complete contact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The study of rubber degradation in automotive components has been reported in the literature such as car wiper rubber blade [5], rubber hoses for car radiators [6] and engine rubber mounting [7]. There are also many studies undertaken on fatigue damage on rubbers materials.…”
Section: Introductionmentioning
confidence: 99%
“…The study of rubber degradation in automotive components has been reported in the literature such as car wiper rubber blade [5], rubber hoses for car radiators [6] and engine rubber mounting [7]. There are also many studies undertaken on fatigue damage on rubbers materials.…”
Section: Introductionmentioning
confidence: 99%